Transformation of zinc oxide nanoparticles under environmentally relevant conditions: influence of pH and ionic strength - Velintine, Valach A.; Boon, Siong Wee; Suk, Fun Chin; Kuan, Ying Kok (Transactions on Science and Technology, 2017)
The demands from nanotechnology industry have been increasing every year. The number of usage of ZnO nanoparticles in the consumer products is also rapidly increasing. The release of nanoparticles to the environment may affect the environment itself and eventually on the human health. Water chemistry such as pH and ionic strength play important roles in the release of Zn ions. In this study, two commercially available zinc oxide (ZnO) nanoparticles of size < 50 nm and < 100 nm were purchased and were characterized by X-ray diffraction (XRD), transmission electron microscopy (TEM), and Fourier transform infrared (FTIR) spectroscopy. XRD and TEM confirmed that the size of the particles was in the range stated at the labels. The dissolutions were measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). It was found that the dissolution is higher at pH 1 and decreased as the pH increased. In terms of ionic strength, small size nanoparticles are stable at lower pH while bigger size is ionic strength dependence.